Bioaugmentation and enhanced formation of biogranules for degradation of oil and grease: Start-up, kinetic and mass transfer studies - Nuid, Maria; Aris, Azmi; Abdullah, Shakila; Fulazzaky, Mohamad Ali; Muda, Khalida (Elsevier, 2023)
Biogranulation technology is an emerging biological process in treating various wastewater. However, the development of biogranules requires an extended period of time when treating wastewaters with high oil and grease (O&G) content. A study was therefore conducted to assess the formation of biogranules through bioaugmentation with the Serratia marcescens SA30 strain, in treating real anaerobically digested palm oil mill effluent (AD-POME), with O&G of about 4600 mg/L. The biogranules were developed in a lab-scale sequencing batch reactor (SBR) system under alternating anaerobic and aerobic conditions. The experimental data were assessed using the modified mass transfer factor (MMTF) models to understand the mechanisms of biosorption of O&G on the biogranules. The system was run with variable organic loading rates (OLR) of 0.69–9.90 kg/m3 d and superficial air velocity (SAV) of 2 cm/s. After 60 days of being bioaugmented with the Serratia marcescens SA30 strain, the flocculent biomass transformed into biogranules with excellent settleability with improved treatment efficiency. The biogranules showed a compact structure and good settling ability with an average diameter of about 2 mm, a sludge volume index at 5 min (SVI5) of 43 mL/g, and a settling velocity (SV) of 81 m/h after 256 days of operation. The average removal efficiencies of O&G increased from 6 to 99.92%, respectively. The application of the MMTF model verified that the resistance to O&G biosorption is controlled via film mass transfer. This research indicates successful bioaugmentation of biogranules using the Serratia marcescens SA30 strain for enhanced biodegradation of O&G and is capable to treat real AD-POME.